APPLICATION OF ISLAMIC FINANCING OPTIONS IN THE OPERATIONS OF YOBE STATE UNIVERSITY COOPERATIVE MULTI-PURPOSE SOCIETY (YSU-CMS) - Adam MUhammad Abubakar (Journal of Islamic Business and Economic Review, 2020)
According to Nigerian Cooperative Societies Act, (2004), a Cooperative Society is a voluntary association of individuals, united by common bond, who have come together to pursue their economic goals for their own benefits. The Islamic co-operative finance system involves coming together to raise halal fund by people of similar ideology and orientation, who contribute their gains in monetary terms to establish a business on profit and loss sharing basis and give loans to members based on mutual understanding without attaching any form of interest. The Yobe State University Cooperative Multi-Purpose Society (YSU-CMS) aims at promoting socio-economic well-being of its members and providing them with economically viable ventures and loan opportunities. This paper aims at assessing the operations of  YSU-CMS in the light of the general principles of Islamic Finance, in order to find out whether it is in conformity with the Islamic teachings or not? In addition, it highlights the general principles that the Islamic co-operative finance system should follow. The researcher adopted analytical and descriptive approaches in this study. The main findings of the paper have shown that some components of YSU-CMS are in conformity with the dictates of Sharia, while others vary. It also revealed that the application of Islamic modes of financing from the angles of Islamic microfinance (ISMF) operations provide base upon which YSU-CMS products can be converted into Shari’ah – compliant products.